Factors Influencing Tuberculosis Infection in Children with Close Contact of Adult Pulmonary Tuberculosis Patients - Fadhliani Putri Mayasri; Wisman Dalimunthe; Pertin Sianturi; Rina Amelia; Rini Savitri Daulay; Fathia Meirina (Jurnal Keperawatan Priority, 2025)
This research aims to determine the factors that influence tuberculosis infection in children with close contact with adult pulmonary tuberculosis sufferers. This research is an analytical observational study with a consecutive sampling method at the Glugur Darat Health Center in November 2024 until January 2025. Bivariate analysis using chi-square to determine whether there is a relationship between the independent and dependent variables. The type of test used is the Fisher Exact and Kruskal Wallis Test. There is no multivariate test because there are no significant variables in the bivariate test. In total, in 42 samples there were 10 children with positive Mantoux tests. Of the 23 female children there were 7 (30.4%) with positive results and of the 19 male children there were 3 (15.8%) positive results. Of the 39 children with a history of BCG immunization, there were 10 (25.6%) with tuberculosis infection. Of the 37 children with parents whose income was <UMR, 10 children (27%) had tuberculosis infection. 37 children whose parents had junior high school education, 9 people (24.3%) had tuberculosis infection. 10 children aged 1-5 years and 6-10 years, there were 2 (20%) each with tuberculosis infection. 26 children aged 11-18 years, there were 6 people (27.3%) with tuberculosis infection. There was no significant relationship between age, gender, immunization status, nutritional status, parental income and parental education level in this research.